Effectiveness of Auxin and Gibberellin Hormone Application on Tomato Plant Growth and Yield (Solanum Lycoprisicum L ) - M Azizi; Yulis Untari; Zaitun Ritaqwin; Firzha Ade Maulina (Warmadewa University Press, 2025)
Tomatoes are one of the most commonly consumed vegetables in the world. Tomatoes are used as a source of vitamins and minerals, among other things. The nutritional content of 100 g of tomatoes is 40 mg of vitamin C, 1500 IU of vitamin A (carotene), 60 ug of vitamin B (thiamine), 4.2 g of carbohydrates, 0.3 g of fat, 1 g of protein, 0.5 mg of iron, 5 mg of calcium, and 27 mg of phosphorus. (27mg). Auxin plays a role in stimulating the cell elongation process. Another function of auxin is to stimulate the cambium to form xylem and phloem. Gibberellin is a hormone that works synergistically with the auxin hormone. Gibberellin affects the development and germination of embryos. This study was conducted in Sp Kelaping Village, Pegasing District, Central Aceh Regency from May 2024 to July 2024. This study used a factorial randomized block design (RAK) with 16 treatments and repeated 3 times to obtain a total of 48 plant units. The data were analyzed using Analysis of Variance (ANOVA), yielding significantly different results, followed by a 5% BNJ analysis. The variables observed included plant height (cm), number of leaves, stem diameter (cm), number of fruits, and fruit weight. Based on the results, it can be concluded that the application of auxin hormone affects the fruit weight of tomato plants at a dose of A3, which is 0.6 ml/L. The application of gibberellin hormone has a very significant effect on the height of tomato plants at 15 days after transplanting at a dose of G2, which is 0.4 ml/L, and has a significant effect on the stem diameter at 15 days after transplanting. The G2 dose was 0.4 ml/L, and had a significant effect on stem diameter at 15 days after transplanting. The A2 dose was 0.4 ml/L, and fruit weight was highest in the G2 treatment, which was 0.4 ml/L